DEVELOPMENT OF NOVEL 1, 3, 4-THIADIAZOLES AS ANTITUBERCULAR AGENTS-SYNTHESIS AND IN VITRO SCREENING - THOMAS, ANCY; B., VINOD; K. U., SNEHA SHENOY; M. V., VISHNU (International Journal of Current Pharmaceutical Research, 2023)
Objective: Tuberculosis, known in short as TB, is considered to be a global crisis caused by Myco bacterium tuberculosis, and which continues to be a serious challenge to public health world wide especially in the developing countries. A serious problem related to tuberculosis is the development of drug resistant strains. Methods: Present study describes the synthesis of eight novel derivatives of 1,3,4-thiadiazole derivatives and in vitro evaluation of their anti tubercular activity against Mycobacterium tuberculosis H37 Rv strain by alamar blue assay. Pyrazinamide and Streptomycin were the standards, used for the evaluation. Results: Among the eight compounds synthesized one derivative was found to be active against the strain tested. All the other derivatives tested exhibited negligible activity against the strain. Conclusion: It can be concluded that novel 1, 3, 4-thiadiazole derivatives can be developed as novel agents in the fight against TB.